miR160: An Indispensable Regulator in Plant - Hao, Kai; Wang, Yun; Zhu, Zhanpin; Wu, Yu; Chen, Ruibing; Zhang, Lei (Frontiers in Plant Science, 2022)
MicroRNAs, recognized as crucial regulators of gene expression at the posttranscriptional level, have been found to be involved in biological processes of plants. Some miRNAs are up- or downregulated during the plant development, stress response and secondary metabolism. Over the past few years, it has been proved that miR160 is directly related to the developments of different tissues and organs in multifarious species, as well as plant-environment interactions. This review highlights recent progress on the contributions of miR160-ARF module to important traits of plants, and the role of miR160-centered gene regulatory network in coordinating growth with endogenous and environmental factors. Manipulation of miR160-guided gene regulation may provide a new method to engineer plants with improved adaptability and yield.